2021
DOI: 10.3847/1538-4357/abcaa6
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fe ii Emission-line Models for AGNs Using New Atomic Data Sets

Abstract: Understanding the Fe II emission from active galactic nuclei (AGNs) has been a grand challenge for many decades. The rewards from understanding the AGN spectra would be immense, involving both quasar classification schemes such as “Eigenvector 1” and tracing the chemical evolution of the cosmos. Recently, three large Fe II atomic data sets with radiative and electron collisional rates have become available. We have incorporated these into the spectral synthesis code Cloudy and examined predictions using a new … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Interestingly, the Fe II/Hβ ratio (Panda et al 2018(Panda et al , 2019a and N V/C IV ratio (Hamann & Ferland 1992Nagao et al 2006) have been suggested to be associated with BLR metallicity. Therefore, the correlation between the Fe II/Mg II ratio and Eddington ratio may suggest that the Fe II/Mg II ratio is also related to BLR metallicity, also supported by theoretical studies (Verner et al 2003;Sarkar et al 2021).…”
Section: Primary Parameter: Eddington Ratio?supporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, the Fe II/Hβ ratio (Panda et al 2018(Panda et al , 2019a and N V/C IV ratio (Hamann & Ferland 1992Nagao et al 2006) have been suggested to be associated with BLR metallicity. Therefore, the correlation between the Fe II/Mg II ratio and Eddington ratio may suggest that the Fe II/Mg II ratio is also related to BLR metallicity, also supported by theoretical studies (Verner et al 2003;Sarkar et al 2021).…”
Section: Primary Parameter: Eddington Ratio?supporting
confidence: 57%
“…However, their modeled emission line strengths of Fe II and Mg II are found to be largely inconsistent (∼1 dex) with the observed line strengths (see Figures 4 and 9 of Sameshima et al 2017), which indicates that their result may not be reliable. The inconsistency can be because their adopted atomic 371-level Fe + model (Verner et al 1999) may be not accurate (see e.g., Verner et al 2003;Smyth et al 2019;Sarkar et al 2021) and/or their parameter space may not reflect the nature of the BLR. Therefore, to confirm the relation between gas density and Eddington ratio, further investigations are required.…”
Section: Physical Implication Of the Relation Between The Blr Metalli...mentioning
confidence: 99%
“…solid angle that is equal to 4 steradians. We utilize a covering factor of 20% that is found to be viable for a near-Keplerian distribution of the BLR clouds (Baldwin, Ferland, Korista, Hamann, & LaCluyzé, 2004;Korista & Goad, 2000;Panda, 2021;Sarkar et al, 2021).…”
Section: Trends and Analysesmentioning
confidence: 99%
“…The adopted SED is the intermediate 𝐿/𝐿 Edd case described by Ferland et al (2020). To be consistent with our previous models we assume a cloud column density of 10 23 cm −2 and use the complete models of Fe emission adopted by Temple et al (2020) and Fe described by Sarkar et al (2021). These data sets are included in the C17.03 download.…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…However, while it is undoubtedly true that the metal content of the BLR gas will have an effect on the observed emission-line ratios, the line emission strengths will also depend on the physical conditions of the emitting gas. For example, Sameshima et al (2017) showed that the lower-ionization line ratio Mg /Fe was strongly affected by the gas cloud density, which needs to be accounted for before inferring the Mg/Fe abundance ratio (see also Sarkar et al 2021). In this paper we demonstrate that the full range of high-ionization broad-line ratios observed in high-luminosity, 𝐿 bol 10 46−47 erg s −1 , quasar spectra with redshifts 𝑧 2, can be explained by varying the physical conditions of the emitting gas, in particular the density and the flux of ionizing photons, without needing to invoke changes in metallicity.…”
Section: Introductionmentioning
confidence: 99%